Empirical research on project success and Knowledge Management (KM) practices in Malaysian Institution of Higher Learning (IHL) - A. Qudaih, Hani; Md., Nasiruzzamn; Ahmad Dahlan, Abdul Rahman (IRPN Publishers, 2013)
The aim of this study is to find out what are the project success factors that may play significant role in knowledge management dissemination through the Malaysian Institute of higher learning. In general this study wish to build a research framework based on a strong theoretical and literature review background. The survey instruments employed in Malaysian Higher learning Institutes knowledge management practices. To show the current situation and future prediction it was necessary to examine variables through Statistical analysis with the software package for windows. This paper reviews and identifies required variables that are associated with the successful knowledge transfer and project success in Malaysians Institutes of Higher Learning (IHL). Knowledge Management Independent variables should reflect successful knowledge transfer and project success, as direct and indirect relationships exist between procure proper knowledge and practices, Strong leadership, Robust ICT Infrastructure, Value based organization, Successful knowledge Sharing and project success. The proposed model idea & elements emerged from successful frameworks and partially tested in Malaysians Institute of higher Learning. Due to the small number of sample size and the convenient method of data collection, the possibility of biases of the authors may play a major role of the study output. The focal objective of the research is that it's proposing a new model for gaining project success through successful knowledge transfer. This study proposed a conceptual framework that requires further exploration and leading away for future research.